Investigation of light polarization in CdS in the presence of two-photon absorption - Kulish, M.R.; Lisitsa, M.P.; Malysh, N.I. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2007)
It is shown that, under the two-photon absorption in CdS, the increase in the
azimuth of polarization causes a smooth change of the large semi-axis angle rotation,
ellipticity, focal parameter, and eccentricity of the polarization ellipse. When the angle of
phase lag δ = 40⁰, the minimum value of ellipticity and the maximal values of focal
parameter and eccentricity will be realized.